Confronting whiteness: Conceptual, contextual, and methodological considerations for advancing ethnic‐racial socialization research to illuminate white identity development. (8th December 2021) - Karras, Juliana E.; Niwa, Erika Y.; Adesina, Fiyinfoluwa; Ruck, Martin D.
Abstract: Beginning with a historical overview of the construction of whiteness, we identify gaps in extant scholarship and provide conceptual, contextual, and methodological considerations for confronting whiteness by advancing critical white ethnic‐racial socialization (ERS) research. First, we consider the mutually influential developmental processes of ERS experiences and the iterative nature of ethnic‐racial identity (ERI) formation among white children and youth. Second, we address how methodological approaches such as person‐centered analysis (PCA) can yield nuanced insight into white ERS processes by helping identify varying developmental pathways that promote antiracist identity development. Third, we highlight the role of online spaces as a formative ecological context through which white children and youth experience ERS processes and the broader societal implications afforded by this context for their ERI development. We conclude with scholarly and practice implications for promoting and supporting antiracist efforts to resist broad‐based historical and current white supremacy.